Protection of polyunsaturated oils against ruminal biohydrogenation and oxidation during storage using a polyphenol oxidase containing extract from red clover - Gadeyne, F.; Van Ranst, G.; Vlaeminck, B.; Vossen, E.; Van der Meeren, P.; Fievez, V. (Food chemistry, 2015)
[Display omitted] •PUFA-rich oils are emulsified using a protein extract from red clover.•Emulsions are protected against ruminal hydrogenation and oxidation during storage.•Protection is achieved by the action of polyphenol oxidase and 4-methylcatechol.•Protection is higher with increasing amounts of diphenol per unit interfacial area.•Protection is suggested to be caused by interfacial protein cross-linking. Polyunsaturated fatty acid (PUFA) are to a large extent subject to biohydrogenation in a ruminal environment, which results to the healthy value of these PUFA being lost upon dietary addition to ruminants. PUFA are also prone to lipid oxidation upon storage. Therefore, it was tested whether emulsions could be protected against in vitro ruminal biohydrogenation and oxidation during storage by using protein extracts rich in polyphenol oxidase, an enzyme responsible for browning of plant tissues. PUFA rich emulsions were made with a protein extract from red clover (Trifolium pratense L.) before adding a synthetic diphenol (4-methylcatechol) to induce protection. Results after in vitro incubation confirmed the hypothesis and indicated the potential to prevent PUFA in linseed or fish oil from ruminal biohydrogenation and oxidation during storage through addition of 4-methylcatechol to the emulsions. Protection depended on the amount of oil present and protein concentrations in the emulsions. Protection efficiency increased with increasing the amounts of diphenol present in the emulsion per unit interfacial surface area. It is suggested that protection is caused by an effective encapsulation by cross-linking of the protein layer at the emulsion interface. For the first time, a method is described to protect PUFA using an enzyme abundantly available in nature, polyphenol oxidase, in combination with 4-methylcatechol.